GENDER DIFFERENCES IN BIG FIVE PERSONALITY TRAITS OF PARTICIPANTS IN KASABEC KABATAAN-BIÑAN CITY: AS A BASIS FOR EFFECTIVE IMPLEMENTATION OF EXTENSION PROGRAMS - Tamban, Victoria Elip; Maningas, Ofelia Borgoños (PEOPLE: International Journal of Social Sciences, 2019)
This study aimed to assess the gender differences in big five personality traits as a basis for effective implementation of extension programs. Descriptive research design was employed in this study. The respondents of the study were 115 participants of extension program in Biñan City. The results revealed that female respondents were about average in terms of openness, conscientiousness, and agreeableness while they were relatively low in terms of extraversion and neuroticism, whereas male were relatively low in terms of openness and conscientiousness while about average in extraversion, agreeableness, and neuroticism. The researchers concluded that gender differences in most of the big five personality traits found significant difference except from agreeableness which did not find a significance, it somehow contradicted to the study of Weisberg, Y., et.al. 2011 wherein their study did not find a significant gender difference in big five personality traits and found significance only in terms of agreeableness. Based on the results of this study the researchers recommended to assess the gender differences of the participants in terms of knowledge, abilities, and skills since abilities and skills are a key element along with the knowledge for the consideration of the skills and qualifications for workers and entrepreneurs.